2005
DOI: 10.1016/j.orl.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Branching rules revisited

Abstract: Mixed integer programs are commonly solved with linear programming based branch-and-bound algorithms. The success of the algorithm strongly depends on the strategy used to select the variable to branch on.We present a new generalization called reliability branching of today's state-of-the-art strong branching and pseudocost branching branching strategies for linear programming based branch-and-bound algorithms. After reviewing commonly used branching strategies and performing extensive computational studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
284
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(294 citation statements)
references
References 6 publications
(8 reference statements)
0
284
0
4
Order By: Relevance
“…Interesting branching strategies suitable for MIQCQP include simple heuristic strategies for determining the variable with the greatest associated error [6,7,18], strong branching [2], violation transfer [133,134], and reliability branching [2,27]. GloMIQO uses reliability branching, a technique that integrates strong branching with a pseudocost heuristic to predict the best branching variable [2,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interesting branching strategies suitable for MIQCQP include simple heuristic strategies for determining the variable with the greatest associated error [6,7,18], strong branching [2], violation transfer [133,134], and reliability branching [2,27]. GloMIQO uses reliability branching, a technique that integrates strong branching with a pseudocost heuristic to predict the best branching variable [2,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As previously mentioned, experiments by Linderoth and Savelsbergh [1999] and Achterberg et al [2005] provided empirical evidence that selecting variable disjunctions on the basis of estimated increase in the lower bound after such a branching could result in a reduction in the number of subproblems solved. Therefore, we base our first criteria for choosing branching disjunctions on the same principle.…”
Section: Branching To Maximize Lower Boundmentioning
confidence: 87%
“…Pseudo-cost branching consists of estimating the change on the basis of the actual change that occurred when the candidate disjunction was previously imposed (in some other subproblem). Recently, Achterberg et al [2005] showed empirically that using a hybrid approach, called reliability branching, yields better results in practice than either of above two approaches used alone.…”
Section: Previous Workmentioning
confidence: 99%
“…As we have just described, an important advantage of our algorithm over its predecessor from Moore and , is the fact that we are not forced to branch after producing an infeasible integer solution and are therefore free to employ the well-developed branching strategies used in algorithms for traditional ILP, such as strong branching, pseudocost branching, or the recently introduced reliability branching [Achterberg et al, 2005].…”
Section: Branchingmentioning
confidence: 99%